The making of a UP UAAP champion baseball team a case study - Isidro, Artemio O. (1980)
The purpose of this study was to document or make a record of how UP baseball team won the 1978 UAAP championship. The writer made a critical analysis of the problem. The conclusions of the the study were: almost every sports team is beset with problems of recruitment, selection and funding; such problems could be licked by establishing link-ups with willing financing institutions; the final reward of a championship title is not an impossible dream; and UP students are able to show their mettle as thinking athletes, with proper emotional background and rigid training.